Evaluating Men with Benign Prostatic Hyperplasia - Lepor, Herbert (MedReviews, LLC, 2004)
The clinical manifestations of benign prostatic hyperplasia (BPH) include lower urinary tract symptoms (LUTS), poor bladder emptying, urinary retention, detrusor instability, urinary tract infection, hematuria, and renal insufficiency. However, the majority of men with BPH present with LUTS only. Because LUTS can indicate a variety of conditions, evaluation of symptomatic men must first aim to identify or exclude BPH and, if present, assess its severity. It is important to assess symptom severity at baseline and during follow-up, using the American Urological Association Symptom Index or the International Prostate Symptom Score. Further testing can then be tailored to narrow the diagnosis and guide treatment decisions. Factors such as patient age and concomitant malignancy will also affect management, but the main goal of treatment remains the improvement of quality of life for the patient.